Classification and scales of Antarctic polar stratospheric clouds using wavelet decomposition - David, Christine; Bekki, Slimane; Berdunov, Nicolai; Marchand, Marion; Snels, Marcellinus; Mégie, Gérard (Journal of Atmospheric and Solar-Terrestrial Physics, 2005)
Polar stratospheric clouds (PSCs) observed with a lidar over the French Antarctic station of Dumont d'Urville (DDU, 66°40' S, 14°01' E) in 1996 are classified using backscatter and depolarisation ratio diagrams. Some Type 1 PSCs, called here intermediate-type PSCs, exhibit lidar signals which do not fit the two distinct groups, Types 1a and 1b, of the standard classification. A wavelet decomposition analysis of backscatter and depolarisation ratio high-resolution profiles is performed in order to study the vertical scales of the various PSC layers. This analysis reveals the presence of small-scale structures in the lidar vertical profiles, which are typical of mesoscale processes associated with the propagation of waves such as gravity waves into the winter stratosphere. When these small-scale structures are filtered out of the lidar profiles, most of the intermediate PSCs detected in the original data disappear, indications that the layers of intermediate PSCs must be relatively thin, possibly embedded into wider synoptic Type 1a or 1b layers. This suggests that intermediate PSCs observed over DDU in 1996 tended to form during rapid and small-scale perturbations associated with mesoscale processes. The lidar signal of intermediate-type PSCs may simply reflect the sampling of rapidly evolving PSCs, supporting the view of these intermediate PSCs as transition-type PSCs. It is worth noticing that the vertical scale of theses processes cannot be fully resolved in meteorological analysis or satellite data. High-resolution data are required to investigate these transition-type PSCs.